PENGARUH SOSIAL EKONOMI KELUARGA DAN PERAN IBU TERHADAP KEBIASAAN SARAPAN PADA SISWA FULLDAY SCHOOL DI SDIT KOTA PEKANBARU - Natalina, Sucita Lestari; Maulida, Fathia (Jurnal Media Informatika, 2024)
Full-day students start activities from morning to afternoon, or around 8 hours at school. By getting used to eating breakfast, you can meet your daily nutritional needs by 15-30%. However, almost 60% of children do not have the habit of eating breakfast for various reasons, and for 66.8%, the nutritional quality of breakfast is still low. This research aims to determine the influence of family socio-economics and the role of the mother on students' breakfast habits. This type of research is observational analytic with a cross-sectional study design. Sampling used the accidental sampling technique to obtain a sample of 81 people. The data collected includes data on children's characteristics, the mother's role in providing food, socio-economic factors, and breakfast habits. Data was collected using a Google form, which was shared via the parents' WhatsApp group. The results showed that the mother's education level and family income level did not influence the mother's role in providing breakfast, with p = 0.292 and p = 0.377. Meanwhile, the mother's employment factor influences the mother's role in providing breakfast with p = 0.018. The mother's role has an influence on students' breakfast habits with p = 0.003. It is recommended for mothers who work outside the home to prepare breakfast early so that the breakfast menu is more varied and complete with vegetables and fruit.